Supply Chain Risk Management Frameworks and Models: A Review - Stavros T. Ponis; Athanasia C. Ntalla (International Journal of Supply Chain Management, 2016)
Supply chain risk management (SCRM) is a relatively new scientific discipline aiming to support management in its everyday struggle against the inherent uncertainty of supply chain operations propagated mostly by demand and supply fluctuations, in terms of yields, capacity, costs and lead times. This paper focuses on a literature review of available SCRM frameworks and models. Using an appropriate combination of keywords, three established academic databases and a hard inclusion criterion, a final sample of 16 (starting from 922) relevant and above all, empirically validated SCRM frameworks/models papers are retrieved and studied in full. Following a systematic literature review approach and supported by a content analysis tool, the authors produce some useful results on the current research status and identify some of its shortcomings, which have to be addressed by researchers in the future, i.e. the immaturity of research in the field, the absence of a holistic approach for SCRM and finally the lack of a systematic approach to successfully identify risk propagation across contemporary and complex supply chain networks.